Differential gene expression at different stages of mesocarp development in high- and low-yielding oil palm - Wong, Yick Ching; Teh, Huey Fang; Mebus, Katharina; Ooi, Tony Eng Keong; Kwong, Qi Bin; Koo, Ka Loo; Ong, Chuang Kee; Mayes, Sean; Chew, Fook Tim; Appleton, David R.; Kulaveerasingam, Harikrishna (BioMed Central, 2017)
Background